OPTIMALISASI KEUNTUNGAN TEMPAT PENCUCIAN SEPATU DENGAN METODE GRAFIK DAN METODE SIMPLEKS - Dimas Dharmawan; Jauhari Arifin (Universitas Putera Batam, 2022)
Optimal profit is the dream of all business owners. The purpose of this study was to determine how to solve the problem of optimization of washing results and to find out the optimal results at the Shoe Store. Kamuuu. Stores need to plan strategies so that all resources can be used appropriately so that optimal washing results. However, the weaknesses faced by MSMEs are very complex, one of which is the lack of profit optimization. This study uses the graphical method and the simplex method, the sample is taken directly from the shop owner. From data collection and processing, POM for Windows software is also assisted to get the maximum profit from the Shoes store. Kamuuu. The results obtained are Rp. 12,600,000.00-, the results are the same as the results of the calculation of the Graphic Method. Compared with the calculation of the Simplex Method, which has a difference of Rp. 1,053,000.00.-